Somalis in Minnesota - Yusuf, Ahmed Ismail (Book collections on Project MUSE., 2013)
The story of Somalis in Minnesota begins with three words: sahan, war, and martisoor. Driven from their homeland by civil war and famine, one group of Somali sahan, pioneers, discovered well-paying jobs in the city of Marshall, Minnesota. Soon the war, news, traveled that not only was employment available but the people in this northern state, so different in climate from their African homeland, were generous in martisoor, hospitality, just like the Somali people themselves. The diaspora began in 1992, and today more than fifty thousand Somalis live in Minnesota, the most of any state. Many have made their lives in small towns and rural areas, and many more have settled in Minneapolis, earning this city the nickname "Little Somalia" or "Little Mogadishu." Amiable guide Ahmed Yusuf introduces readers to these varied communities, exploring economic and political life, religious and cultural practices, and successes in education and health care. he also tackles the controversial topics that command newspaper headlines: alleged links to terrorist organizations and the recruitment of young Somali men to fight in the civil war back home. This newest addition to the people of Minnesota series captures the story of the state's most recent immigrant group at a pivotal time in its history.